2016
DOI: 10.1136/jech-2016-207404
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of individuals' participation in integrated chronic disease screening in Singapore

Abstract: Our study suggests that ethnicity, education, family cohesion, healthy behaviour patterns and perceived physical health status were key determinants of health screening participation. Enhancing the cultural competence of preventive health services may help increase participation of these groups in screening efforts and reduce the proportions of undiagnosed chronic disease in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
3
10
0
Order By: Relevance
“…Also, consistent with the present findings, previous studies have shown that older age groups present with higher prevalence rates of preventive health-care utilization than their younger counterparts and that community dwelling elderly demonstrate need for preventive oral-health care (35,7). In contrast, DE BOER, (44) found no significant influence of age, suggesting that the direction of age influence depends on specific characteristics of the study population.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Also, consistent with the present findings, previous studies have shown that older age groups present with higher prevalence rates of preventive health-care utilization than their younger counterparts and that community dwelling elderly demonstrate need for preventive oral-health care (35,7). In contrast, DE BOER, (44) found no significant influence of age, suggesting that the direction of age influence depends on specific characteristics of the study population.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have applied Andersen's model in a variety of contexts, including oral health, lending support to the model's hypothesized relationships . The present findings agree with evidence suggesting that health‐care utilization in older people varies according to individual and contextual factors . Using structural equation modelling, Baker revealed that the impact on use of oral health‐care services from predisposing factors was indirect and mediated through enabling resources.…”
Section: Discussionsupporting
confidence: 87%
“…The Anderson model of healthcare-use behaviour [ 16 ] was used to identify potential determinants of cancer screening awareness and participation. This model includes three domains: predisposing, enabling, and need factors, which interact in determining one’s health-related behaviour.…”
Section: Methodsmentioning
confidence: 99%
“…Univariable analyses were conducted for all potential determinants of cancer screening awareness and practice. These factors comprised different components of the Anderson model [ 16 ], ranging from predisposing factors such as sociodemographic characteristics (e.g. marital status, education, income), enabling factors, which included healthcare access.…”
Section: Methodsmentioning
confidence: 99%
“…Venkataraman et al () investigated 6,366 Singapore residents and identified several factors associated with greater health screening participation: an older age, Chinese or Indian ethnicity, higher education levels, and leisure‐time physical activity. Varga and Surratt () investigated 546 Black, street‐based female sex workers and found that access to fixed medical facilities or permanent physicians was a factor influencing the use of preventive health services.…”
Section: Introductionmentioning
confidence: 99%